1998
DOI: 10.1016/s0375-9601(97)00874-8
|View full text |Cite
|
Sign up to set email alerts
|

On the role of density inhomogeneity and local anisotropy in the fate of spherical collapse

Abstract: We obtain an expression for the active gravitational mass of a collapsing fluid distribution, which brings out the role of density inhomogeneity and local anisotropy in the fate of spherical collapse.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 16 publications
4
103
0
Order By: Relevance
“…The noticeable behavior of the "effective inertial mass" as named by m T played with an extension on the universal theory of energy for the local surface , the detail is given in [8,18,19] …”
Section: The Formulation Of Tolman Mass and The Mass Functionmentioning
confidence: 99%
“…The noticeable behavior of the "effective inertial mass" as named by m T played with an extension on the universal theory of energy for the local surface , the detail is given in [8,18,19] …”
Section: The Formulation Of Tolman Mass and The Mass Functionmentioning
confidence: 99%
“…Also, from the field equations and the definition of the Weyl tensor it can be easily shown that (see [21] for details)…”
Section: The Weyl Tensormentioning
confidence: 99%
“…The investigation of the final stellar phase has been a focus of great interest for many relativistic astrophysicists and gravitational theorists. In this respect, various authors [54][55][56][57] explored the problem of GC by taking some realistic configurations of matter and geometry. In the context of f (R) gravity, various results have been found in the literature as regards collapsing stellar interiors and black holes [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%